PENGARUH KINERJA KEUANGAN TERHADAP KEMAMPUAN MEMBAYAR ZAKAT PERUSAHAAN - Helvy Rafika Krisdiyanti; Titi Rapini; Umi Farida (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This research was conducted at Hasby Ponorogo convection company. The purpose of this study is to determine the effect of financial performance on the ability to pay zakat. Analysis methods used are the classic assumption test, multiple linear regression and hypothesis testing. Data processing using SPSS version 16. The result of the study showed that the Profitability Ratio (Return On Asset) had a positive effect on the company zakat, the Liquidity Ratio (Current Ratio) and the Activity Ratio (BOPO) had no effect on the company zakat. Regression result show that adjusted r square is 0.838, meaning that the influence of independent variables on the dependent variable is 83.3% and 16.2% is influenced by other variables not included in this research model.